Labor economics in Germany: retrospect and contemporary state - ГерлахK.; Мейер, В. (Вестник ВГУ. Серия: Экономика и управление, 2006)
In this article a brief overview of labor economics in Germany is presented. The starting point is the divergent development of labor economics in Germany and the Anglo-American countries. Subsequently, the fi rst steps of the new discipline emerging after the second world war in Germany are discussed and the most blatant research gaps in the 1970s are identifi ed. The most extensive section of the paper is devoted to the actual state of labor economics. The key actors of labor research are presented, data and methods briefl y discussed and the outstanding contemporary research areas are outlined. Needless to say, a subjective assessment is unavoidable in the delineation of the principal research areas. After a short characterization of the most widely used textbooks the concluding remarks are presented.